Effects of select menhaden fish meal fed during lactation on sow and litter performance - Musser, R.E.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 317 lactating sows was fed either a corn-soybean meal diet (l.0%lysine) or a diet with a portion of the soybean meal replaced with 5% select menhaden fish meal on an equal lysine basis. Adding 5% select menhaden fish meal had no overall effect on sow or litter performance. Composition of milk samples collected between d 14 and 16 of lactation was not affected by dietary treatment.
Keywords: Swine; Sows; Lactation diets; Select menhaden fish meal